Assessment of pulmonary artery stiffness by multiparametric cardiac magnetic resonance-surrogate for right heart catheterization - Körperich, Hermann; Eckstein, Jan; Atito, Medhat; Barth, Peter; Laser, Kai Thorsten; Burchert, Wolfgang; Weber, Oliver M.; Stehning, Christian; Piran, Misagh (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiac magnetic resonance (CMR) imaging allows for multiparametric assessment of healthy pulmonary artery (PA) hemodynamics. Gender-and aging-associated PA stiffness and pressure alterations have remained clinically unestablished, however may demonstrate epidemiological differences in disease development. The aim of this study is to evaluate the role of CMR as a surrogate for catheter examinations by providing a comprehensive CMR assessment of sex-and age-related reference values for PA stiffness, flow, and pressure.Results: PA hemodynamics were studied between gender and age groups (>/< 50 years) using phase-contrast CMR. Corresponding correlation analyses were performed. 179 healthy volunteers with a median age of 32.6 years (range 11.3 to 68.2) were examined. Males demonstrated increased PA compliance (median [interquartile range] or mean ± standard deviation) (20.8 mm²/mmHg [16.6; 25.8] vs. 19.2±7.1 mm²/mmHg; p< 0.033), higher pulse wave velocity (2.00 m/s [1.35; 2.87] vs. 1.73 m/s [1.19; 2.34]; p=0.018) and a reduced full width half maximum (FWHM) (219±22 ms vs. 235±23 ms; p<0.001) than females. Mean, systolic, diastolic PA pressure and pulmonary proportional pulse pressure were significantly elevated for males compared to females (p<0.001). Older subjects (>50 years) exhibited reduced PA elasticity (41.7% [31.0; 52.9] vs. 66.4% [47.7; 83.0]; p<0.001), reduced PA compliance (15.4 mm²/mmHg [12.3; 20.7] vs. 21.3±6.8 mm²/mmHg; p<0.001), higher pulse wave velocity (2.59 m/s [1.57; 3.59] vs. 1.76 m/s [1.24; 2.34]; p<0.001) and a reduced FWHM (218±29 ms vs. 231±21 ms; p<0.001) than younger subjects. Conclusions: Velocity-time profiles are dependent on age and gender. PA stiffness indices deteriorate with age. CMR has potential to serve as a surrogate for right heart catheterization.